Implementation and evaluation of a novel orientation manual for the emergency medicine clerkship and elective rotation - Terry, Sydney; Feldman-Kiss, Damian; McInnes, Gord (Canadian Medical Education Journal, 2025)
Implication Statement The Kelowna General Hospital (KGH) Emergency Medicine (EM) Orientation Manual (OM) is a 28-page, mobile-friendly resource designed for medical students to use on- and off-shift. It contains all the academic, clinical, and logistical information needed for the KGH EM rotation, minimizing extrinsic cognitive load while equipping junior learners with tools to enhance learning and performance. The OM is adaptable to other sites by modifying the site-specific information while preserving the EM educational content. If it is replicated, we anticipate similar benefits in subjective medical student preparedness, performance, and experience while generally decreasing their preparation time for the EM rotation.